Trend on sales performance of small and medium enterprise trade fair participants - Cabaron, Jennifer B. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2016)
This study conducted in Zamboanga Peninsula looked into effects to sales of SMEs after participating in trade fairs. It also determined the correlation between the frequency of SMEs attendance in trade fairs and the frequency in increase of sales. Descriptive – survey method was used aided with the questionnaire and interviews. From the interview, the researcher hereby concluded that SMEs operate mainly on the local markets and besides some of them were not able to participate all the trade fairs due to lack of budget for the product exhibitions and booth expenses. The study revealed that there were businesses that attended trade fairs only once and that increased their sales. Others kept on attending trade fairs and it increased eventually. It is only on the ninth time when the trade fair was conducted that most of the attendees have just made it to break-even point. Results showed moderate correlation between attendance to trade fairs and the business sales performance. Expenses incurred in attending trade fairs were constraints identified by SMEs.